Keikutsertaan Program Asuransi Usaha Tani Padi (AUTP) di Pekon Tulung Agung Kecamatan Gadingrejo Kabupaten Pringsewu - Maria Ditha Ayu Suari; Dame Trully Gultom; Sumaryo Gitosaputro (Fakultas Pertanian Universitas Jember, 2021)
The purpose of this study is to : 1) knowing the adoption rate of the AUTP Program, 2) analyzing factocrs that affect the adoption rate of the AUTP Program, 3) knowing the obstacles faced by farmers in adopting the AUTP Program. This study uses a survey methods on farmers who are members of farmers group and follow the AUTP Program. Respondents to this study numbered 39 farmers. Data analysis methods use descriptive analysis and multiple linear regression analysis. The results of this study show that the adoption rate of the AUTP Program in Pekon Tulung Agung, Gadingrejo District, Pringsewu Regency belongs to the low category for the growing season indicators included, while for indicators of the area of insured land is still in the moderate category, factors that have a real effect on the adoption rate of the AUTP Program include the level of complexity of the AUTP Program, the social environmental influence of farmers, and the role of the extension as a facilitator. The obstacles faced by farmers in adopting the AUTP Program lie at the time of registration and filing of claims. Keyword: Adaption rate, AUTP Program